Pengaruh Kecerdasan Emosional, Budaya Organisasi, Komunikasi Dan Disiplin Kerja Terhadap Kinerja Pengurus Organisasi Daerah (Studi Kasus Komunitas Mahasiswa Pamekasan Periode 2022-2023) - Sulaiman, Sulaiman; Basalamah, Muhammad Ridwan; Normaladewi, Andi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to determine the effect of emotional intelligence, organizational culture, communication and work discipline on organizational performance in Pamekasan Student Community administrators. The location of this research was conducted at the Pamekasan Student Community management. This research is quantitative research. This research uses an explanatory research method. This research uses a case study method where the data is obtained by distributing questionnaires to the Pamekasan Student Community management. Sampling using nonprobability sampling technique, namely saturated sampling and obtained results as many as 67 respondents. The data was analyzed using multiple linear regression tests and determination tests. Based on the results of data analysis, the t test results show that emotional intelligence, organizational culture, communication and work discipline partially have a significant positive effect on the performance of the Pamekasan Student Community management. The results of the determination test show that the percentage is 42%, which means that the performance of the board can be influenced by emotional intelligence, organizational culture, communication and work discipline. Keywords : Management Performance, Emotional Intelligence, Organizational Culture, Communication, Work Discipline.